Effective irradiation of high-power RF pulses from gyromagnetic nonlinear transmission lines; Pulsed Power Conference (PPC) - Romanchenko I. V. Ilya Viktorovich; Rostov V. V. Vladislav Vladimirovich; Klimov A. I. Aleksey Ivanovich; Kurkan I. K. Ivan Konstantinovich; Gunin A. V. Alexander Vladimirovich; Кошелев В. И. Владимир Ильич; Sukhushin K. N.; Andreev Yu. A.; Konev V. Yu. Vladimir Yurievich (2013, 2013)
Title screen